Implementasi Kode Etik Guru Di Sekolah Dasar Dan Pengembangan Etika Pofesi Berkelanjutan - Muasyaroh, Syifa; Safira, Nazwa; Hapidoh, Siti (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The teacher’s code of ethics serves as a moral and professional guideline that directs teachers’ attitudes and behavior in carrying out their educational duties. The implementation of the teacher’s code of ethics in elementary schools plays a crucial role, as teachers act as primary role models in shaping students’ character from an early age. This study aims to examine the implementation of the teacher’s code of ethics in schools and the development of sustainable professional ethics. This research employs a qualitative approach using a literature review method. Data sources were obtained from relevant books and scientific journal articles related to the teacher’s code of ethics and professional ethics. Data were collected through literature searching, selecting, and recording key information, and analyzed using content analysis. The findings indicate that the implementation of the teacher’s code of ethics in elementary schools contributes to improving teacher professionalism, creating a safe and conducive learning environment, and fostering positive student character development. Continuous development of teachers’ professional ethics is essential through training, self-reflection, teacher working groups, supervision, and strengthening a culture of role modeling to ensure ethical values are consistently internalized in educational practice.